PEREKAM/PEMUTAR SUARA DIGITAL BERKAPASITAS BESAR UNTUK APLIKASI EMBEDDED SYSTEM - - Yoppy; Waru Djuriatno; - Suprapto (Widyariset, 2010)
In embedded-system designs that involve just a small capacity voice-recorder, one may use EEPROM or voice-recorder IC. However, sometimes one needs a high capacity voice recorder also. In this case, EEPROM can’tfulfill the needs anymore because it’s hard to get EEPROM with capacity even at 512 kbyte. Meanwhile, the ISD® voice-recorder IC could store voice up to 16 minutes only. For this background, the writer proposes a high-capacity digital voice recorder which is able to record voice for several hours. It uses SD Card as the storage media.. With sampling rate at 8 kHz/8 bit and 512 MB SD Card, the recorder can store voice until 18 hours. The recorded voices are stored in WAV file format so that can be transfered from and to PC when needed.